Ranma 1/2. Vol. 6 - Takahashi, Rumiko, 1957- (Viz graphic novel., 1996)
Just when Ranma thought his life was calming down, he has to deal with a bathhouse battle, a freaky panty thief, a woman-crazy master, and the dreaded Dojo Destroyer.